2015
DOI: 10.4025/actascihealthsci.v37i2.23444
|View full text |Cite
|
Sign up to set email alerts
|

<b>Prevalence of variant hemoglobins and thalassemias in a maroon community in Sergipe, Brazil

Abstract: ABSTRACT. Current analysis investigates the sickle-cell syndrome among members of a maroon community (comunidade quilombola) in the state of Sergipe, Brazil. The entire population, comprising five hundred and ninety-three people, was screened. Blood samples were collected from 318 people, aged between six months and fifty years, who underwent a solubility test to assess the presence of HbS, followed by Sickle-Cell Test to confirm its presence. Results revealed that 2.2% of the three hundred and eighteen people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Conversely, Santos et al 16 found little difference in the social relations and psychological domains, reporting hypertension and QoL in quilombas. Assis et al 18 identified worse averages for the psychological domain in retired or pensioner quilombas and women.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Conversely, Santos et al 16 found little difference in the social relations and psychological domains, reporting hypertension and QoL in quilombas. Assis et al 18 identified worse averages for the psychological domain in retired or pensioner quilombas and women.…”
Section: Discussionmentioning
confidence: 97%
“…One possible explanation for the satisfaction identified in this domain may be average age (young elderly persons), as the functional capacity of the elderly has not yet been impaired and positively influences the perception of QoL. Assis et al 18 observed a correlation between age and the physical domain among quilomba communities investigated in Sergipe.…”
Section: Discussionmentioning
confidence: 99%
“…G6PDd is an X chromosome-linked enzymopathy determined by missense single nucleotide variants (SNVs) in the G6PD gene (Howes et al 2013). Two known G6PD variants of African origin have clinical importance: G6PD*A (determined by the SNP rs1050829, a c.376 T > C mutation), and AMD, Abobral Margem Direita; AME, Abobral Margem Esquerda (Schneider et al 1987;Bortolini et al 1992Bortolini et al , 1998Arpini-Sampaio et al 1999;Guerreiro et al 1999;Oliveira et al 2002;De Mello Auricchio et al 2007;Cardoso et al 2012;de Souza et al 2013;De Assis et al 2015;Dantas et al 2016;Santiago et al 2017;Teles et al 2017) G6PD*A-(determined by rs1050829 and a second mutation: rs1050828 (c.202C > T), rs137852328 (c.680G > T), or rs76723693 (c.968 T > C)). Besides being associated with protection against malaria infection, G6PDd is of great public health importance in malaria-endemic regions, such as the Brazilian Amazon, for causing hemolytic crises induced by antimalarial drugs-such as primaquine-in G6PD deficient individuals.…”
Section: African Adaptations In the Brazilian Environmentmentioning
confidence: 99%